Pengaruh Kecanggihan Teknologi Informasi Dan Kemampuan Teknik Personal Terhadap Efektivitas Penggunaan Sistem Informasi Akuntansi Pada PT Bank Rakyat Indonesia - Yuan Nanda, Mike; Wisnu Pranoto, Fatwa; Agustin, Fitri; Ermayanti , Dwi (Universitas Indo Global Mandiri, 2024)
At this time, information technology is experiencing quite rapid development. Apart from developments in the types of technological equipment and supporting application software, this development is also based on the increasingly equitable use of technological information. In the current era of globalization, competition between companies is increasingly fierce, which encourages every company to implement information systems that can support the company's operational capabilities effectively, efficiently and under control so as to create a competitive advantage. Computerized user systems in processing company data are a manifestation of the rapid development of technology and information. This is used to support operational activities in order to produce appropriate and beneficial decisions for the company. This research aims to analyze the influence of information sophistication on the effectiveness of using the accounting information system at PT Bank Rakyat Indonesia. A sample is a part of the population taken based on certain calculations, to be used as material that will be researched optimally. The samples taken are based on the underlying theory because this sample represents the research object from the existing population. This research uses a quantitative descriptive approach with a method using purposive sampling techniques, with 45 respondents indicating that the sophistication of information technology and personal technical abilities have a significant positive effect on the effectiveness of using accounting information systems. The results of data analysis and classical assumption tests confirmed statistical suitability. The implication is that the influence of sophisticated information technology and personal technical abilities can jointly increase the effectiveness of accounting information systems. Keywords: sophistication of information technology, personal technical abilities, effectiveness